2018
DOI: 10.1002/mds.27336
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime exposure to estrogen and progressive supranuclear palsy: Environmental and Genetic PSP study

Abstract: This case-control study suggests a protective role of lifetime estrogen exposure in PSP. Future studies will be needed to confirm this association. © 2018 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…CES totals ranged from 0 to 5. Hysterectomy is most commonly indicated for fibroids, which are benign tumors that are dependent on estrogen presence (14,15). Thus, hysterectomy without oophorectomy serves as a surrogate marker of estrogen exposure and was included in the CES as in previous similar composite scores (13,16).…”
Section: Methodsmentioning
confidence: 99%
“…CES totals ranged from 0 to 5. Hysterectomy is most commonly indicated for fibroids, which are benign tumors that are dependent on estrogen presence (14,15). Thus, hysterectomy without oophorectomy serves as a surrogate marker of estrogen exposure and was included in the CES as in previous similar composite scores (13,16).…”
Section: Methodsmentioning
confidence: 99%
“…Age at menopause was estimated using the age at the last menstrual cycle or at the time of bilateral oophorectomy. Lifetime exposure to estrogen (estrogen exposure length) was the sum of difference between age at menopause and menarche (reproductive years) and years of estrogen replacement therapy (ERT) use 12 . The estrogen deprivation length was the difference between age at PD onset and estrogen exposure length.…”
Section: Methodsmentioning
confidence: 99%
“…Lower education levels (high school completion or lower versus college completion or higher) are associated with incident PSP, and studies have indicated associations with duration of exposure to well water and industrial waste. In a study of 150 women with clinically diagnosed PSP and 150 age-matched control women, any exposure to estrogen replacement therapy was associated with a halved risk of PSP (odds ratio, 0.52; 95% CI, 0.30-0.92; P =.03) 6 …”
Section: Progressive Supranuclear Palsymentioning
confidence: 99%